Effects of a Teaching Personal and Social Responsibility Model Intervention in Competitive Youth Sport - Carreres-Ponsoda, Federico; Escartí, Amparo; Jimenez-Olmedo, Jose Manuel; Cortell-Tormo, Juan M. (Frontiers in Psychology, 2021)
The aim of this study was to implement the TPSR model in a competitive context analysing the differences between the intervention and the control group on personal and social responsibility, prosocial behaviours and self-efficacy in youth soccer players. Participants were 34 youth soccer players between the ages of 14 and 16 years old (15.18±0.72) divided into two different soccer teams of 17 members, corresponding to the control and intervention group. The implementation of the TPSR model took place during nine months, including initial and ongoing coach training (3 months), program implementation (3 sessions per week lasting 90 minutes during 6 months) and a series of expert-led seminars for athletes (1 session per week lasting 90 minutes during 4 months). The questionnaires used to collect data were the Spanish validations of the Personal and Social Responsibility Questionnaire (Escartí, Gutiérrez and Pascual, 2011), Prosocial Behaviour Scale (Del Barrio, Moreno and López, 2001) and two Children’s Self-efficacy Scales (Carrasco and del Barrio, 2002). Results indicated that the TPSR intervention group obtained an increase in post-test levels of personal and social responsibility, prosocial behaviour and self-efficacy due to the application of the TPSR model compared with control group that used a conventional sport teaching methodology. The conclusion is that TPSR model have the potential to be adapted and implemented with flexibility in youth sport competition contexts in order to improve personal and social responsibility, prosocial behaviour and self-efficacy.